A irradiação da estrutura dentária modifica o resultado da saturação de oxigênio aferida pelo oxímetro de pulso? - Santana, Maria Luiza Lima (2022)
Objective: To evaluate the interference of dental structure ionizing radiation in measuring finger oxygen saturation by a pulse oximeter. Materials and method: Fifty-four extracted human third molars were sectioned mesiodistally to obtain the buccal and palatal/lingual surfaces standardized in 4,0mm of thickness, involving enamel and dentin structure. The initial measurement of oxygen saturation (SaO2) and heart rate (bpm) of the little finger of the participant's hand, at rest, was performed using the portable pediatric pulse oximeter BCI 3301 (positive control before ionizing radiation). As a negative control, oxygen saturation was measured with the faces of the teeth juxtaposed to each other. Next, the faces of the teeth were fixed parallel to the pulse oximeter diodes and interposed between the participant's minimum and the pulse oximeter diodes for pre-irradiation data collection. For this, an additional silicone mold was used to fix the pulse oximeter diodes to be parallel and set in a vise-type vise. The recording of SaO2 was carried out in the presence and absence of ambient light. Afterward, the sample received the ionizing radiation in a fractional form, from 2Gy daily, 5 days a week, for 7 weeks, up to 70Gy. For post-irradiation evaluation, a new positive control was performed and then the measurement of SaO2 values was performed following the protocol previously described. The Kolmogorov Smirnov test analyzed the normality relationship of the quantitative variables described through the mean and standard deviation. To compare the mean values of oxygen saturation before and after irradiation, in the presence and absence of light, the Student's t-test for paired samples was used. A 95% confidence interval and a 5% significance level were considered. Results: The mean values of SaO2 in the positive controls were 96.95±0.6% in the presence of light and 96.85±0.7% in the absence of light. For the analysis of SaO2 before irradiation, mean values of 94.7±0.6% were obtained in the presence of light and 93.2±1.3% in the absence of light, with a significant reduction in these values compared to positive pre-irradiation controls (p<0.001). After irradiation, the mean SaO2 value was 94.6±0.9% in the presence of light, with no statistically significant difference (p=0.623) when compared to the pre-irradia tion value, while in the absence of light the value mean of SaO2 was 93.7±0.9%, with a statistical difference when compared to before irradiation (p=0.024). Conclusion: The change in tooth structure caused by ionizing radiation does not interfere with pulse oximeter measurement in the presence of light. Although light influences pulse oximeter results, its difference does not represent clinical relevance.